Who is buying electric vehicles in California? Characterising early adopter heterogeneity and forecasting market diffusion. (September 2019) - Lee, Jae Hyun; Hardman, Scott J.; Tal, Gil
Abstract: The successful market entry of plug-in electric vehicles (PEVs) is contingent on them being adopted by consumers, the first of which will be early adopters. The current understanding of these early adopters is based on small samples of PEV buyers gathered at one point in time. Here we present multi-year (2012–2017) questionnaire survey data on the socio-demographic profile of 11, 037 PEV adopters in California. Latent class cluster analysis reveals four heterogeneous groups of PEV buyers. 49% are High income families, 26% Mid/high income old families, 20% Mid/high income young families, and about 5% are Middle income renters . Using the latent classes as input factors in Bass diffusion models we show that high income families may not continue to be the largest group of PEV adopters, while high income families are 49% of the PEV market today, they only represent 3.6% of California households. For market growth to continue the mid/high- and middle-income clusters need to begin adopting PEVs in greater numbers than they are doing today. Policymakers will need to consider the different needs these consumers have for infrastructure and incentives compared to high income families .